2005
DOI: 10.1016/j.jcrs.2005.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Clear corneal paracentesis: A case of chronic wound leakage in a patient having bimanual phacoemulsification

Abstract: endophthalmitis. Ophthalmology 1991; 98:639-649; discussion, 650 5. Bannerman TL, Rhoden DL, McAllister SK, et al. The source of coagulase-negative staphylococci in the Endophthalmitis Vitrectomy Study; a comparison of eyelid and intraocular isolates using pulsed-field gel electrophoresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Some studies found that the degree of induced astigmatism after bimanual MICS is equal to or even less than that of conventional coaxial small incision cataract surgery [4,7,19,23] and that the tissue damage from bimanual MICS is comparable to that from small incision cataract surgery [19,[23][24][25][26][27] . However, there are some disadvantages to B-MICS including wound damage, difficulties in mastering the technique, leakage due to thermal burn and the need for wound enlargement for IOL implantation [2,5,10,28,29] . C-MICS does not have the above-mentioned disadvantages and can therefore be easily and safely performed by most surgeons [28,[30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that the degree of induced astigmatism after bimanual MICS is equal to or even less than that of conventional coaxial small incision cataract surgery [4,7,19,23] and that the tissue damage from bimanual MICS is comparable to that from small incision cataract surgery [19,[23][24][25][26][27] . However, there are some disadvantages to B-MICS including wound damage, difficulties in mastering the technique, leakage due to thermal burn and the need for wound enlargement for IOL implantation [2,5,10,28,29] . C-MICS does not have the above-mentioned disadvantages and can therefore be easily and safely performed by most surgeons [28,[30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that surgically induced astigmatism (SIA) and corneal aberrations after bimanual MICS, are slight. [19][20][21][22] However, there are major disadvantages to bimanual MICS, including difficulty learning the surgical technique, 23,24 the possibility of wound leakage, 23,24 and subsequent endophthalmitis 25 due to thermal burn. 26 Furthermore, it is often necessary to enlarge the wound to approximately 2.0 mm for IOL insertion because IOLs that can be inserted through a sub-2.0 mm incision are still evolving.…”
Section: J Cataract Refract Surg 2009; 35:233-239 Q 2009 Ascrs and Escrsmentioning
confidence: 99%
“…5 The short-length and single-plane incisions of bimanual microincision surgery have been cited as a cause of endophthalmitis 20 and persistent wound leak. 21 Microcoaxial phacoemulsification requires an incision of less than or equal to 2.2 mm and accommodates a sleeve over the tip. This allows aspiration and irrigation through the same incision coaxially and allows implantation of an IOL without enlarging the incision.…”
Section: J Cataract Refract Surg 2007; 33:1019-1024 Q 2007 Ascrs and mentioning
confidence: 99%